Pengaruh Pelatihan Packaging, Inovasi Dan Motivasi Terhadap Kualitas Produk Dengan Brand Image Sebagai Variabel Intervening Pada Pelaku Usaha Industri Kecil Dan Menengah (IKM) Binaan Dekranasda Provinsi Kepulauan Riau - Dianalfianti, Zurfiera; Satriawan, Bambang; Puspita Dewi, Nolla (Program Studi Manajemen FEBM UMRAH, 2025)
Many Small and Medium Enterprises (SMEs) in the Riau Islands face obstacles in meeting product standardization, particularly related to production facilities that do not meet Good Manufacturing Practices (GMP) standards. This hinders their ability to export, despite government support to facilitate SMEs in licensing and development. This research is intended for explanatory or confirmatory purposes, namely to explain the causal relationships between variables through hypothesis testing. Based on the results of the research data analysis above, the following conclusions can be drawn from this study: Training, innovation, and motivation have a significant influence on product quality. Innovation does not significantly influence product quality. Training and innovation have a significant influence on product quality through the path coefficient results, while motivation does not have a significant influence on product quality through the path coefficient results.